수학교과교육학 및 교과내용학 강좌의 대면 및 비대면 운영 결과 비교 분석 - 서보억; Boeuk Suh (과학교육연구지, 2021)
본 연구는 예비수학교사 대상의 수학교육론과 미적분학 강좌를 비대면수업으로 진행한 결과와 대면 수업으로 진행한 결과 사이의 차가 무엇인지를 살펴보기 위한 목적으로 진행하였다. 본 연구의 대상인 ‘수학교육론’ 및 ‘미적분학’ 강좌의 비대면수업은 ‘비대면수업 수업설계 모형’에 근거하여 계획, 개발, 실행되고 평가하였다. 본 연구를 통해 수학교과교육학 및 수학교과내용학 강좌운영에서 ‘비대면수업/혼합수업’과 ‘대면수업’의 차이가 무엇인지 살펴보았고, 수학교과교육학 과목과 수학교과내용학 과목에 대한 비대면수업에 대한 학생들의 인식을 조사하였으며, ‘수학교육론’ 강좌와 ‘미적분학’ 강좌에서 비대면수업과 대면수업에서 평가결과의 차가 있는지 분석하였다. 향후 예비수학교사교육에서 비대면수업 및 혼합수업 역량이 향상될 수 있는 기회를 제공하고, 지속적인 연구가 수행되길 기대한다. This study explores classes for pre-service mathematics teachers. The purpose of this study is to examine the differences between ‘non-face-to-face’ classes & ‘face-to-face’ classes, as well as the differences in learning outcomes between these two methods. A Professors' Learning Group was formed to effectively carry out this study. Through this learning group, we shared how to plan and operate the lecture. The subjects of this study are ‘non-face-to-face calculus courses & face-to-face calculus courses’ and ‘non-face mathematics education theory courses & face-to-face mathematics education theory courses." Specifically, in these two pairs of courses, we analyze the differences in course management and the differences in the outcomes of students' assessments. Non-face-to-face classes were planned, developed, implemented and evaluated based on the 'non-face class design model.' The results of this study are as follows: First, we explored the differences between 'non-face-to-face classes/mixed classes' and 'face-to-face classes.' Second, the achievement results in calculus courses were higher in face-to-face classes than in non-face classes. Third, the results of achievements in mathematics education theory courses were higher in mixed classes than in face-to-face classes. Through the results of this study, we hope that the non-face-to-face class capabilities can be improved in pre-service mathematics teacher training.